2002
DOI: 10.1159/000048582
|View full text |Cite
|
Sign up to set email alerts
|

MEN 10700, a New Penem Antibiotic: In vitro Antibacterial Activity on Clinical Isolates

Abstract: MEN 10700 is a new broad-spectrum penem, currently in preclinical development. In the present study, the activity of MEN 10700 was compared to that of imipenem, meropenem, cefotaxime, ampicillin/sulbactam, amikacin and ciprofloxacin against 619 gram-positive and gram-negative bacterial strains, and to that of imipenem, meropenem, cefotaxime, ceftriaxone, ceftazidime, cefepime and ampicillin/sulbactam against 38 strains of ciprofloxacin-resistant Escherichia coli, and against 19 extended-spectrum-β-lactamase (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Imipenem is a new carbapenem with a broad spectrum of activity against Gram-positive, Gram-negative, aerobic and anaerobic bacteria, including strains resistant to multiple drugs [1] . Imipenem when administrated alone was nephrotoxic due to hydrolysis by dehydropeptidase I, but this problem has been solved by coadministration of cilastatin, an efficient inhibitor of dehydropeptidase I [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Imipenem is a new carbapenem with a broad spectrum of activity against Gram-positive, Gram-negative, aerobic and anaerobic bacteria, including strains resistant to multiple drugs [1] . Imipenem when administrated alone was nephrotoxic due to hydrolysis by dehydropeptidase I, but this problem has been solved by coadministration of cilastatin, an efficient inhibitor of dehydropeptidase I [2] .…”
Section: Introductionmentioning
confidence: 99%
“…13 Another study showed that MEN 10700 had similar MICs to those of meropenem and imipenem in most gram-positive and gram-negative clinical isolates tested, with the exceptions of Morganella morganii, Serratia marcescens, and Acinetobacter sp, where MICs were lower for the carbapenems. 21 The greatest bactericidal effects of MEN 10700 were seen 4-6 hours after incubation with bacterial cultures, at which time a 2-3 and 3-4 log decline in colony-forming units was observed at 2 and 4-8 times the MIC of MEN 10700, respectively. 14 This rapid and potent bactericidal effect might be accounted for by the high affinity of MEN 10700 for PBP2 and PBP1a/b (concentration for 50% inhibition of penicillin binding [IC 50 ] = 0.1 and 1 mg/L, respectively) as revealed by competition experiments using membranes isolated from Escherichia coli.…”
Section: Men 10700mentioning
confidence: 96%
“…14 This rapid and potent bactericidal effect might be accounted for by the high affinity of MEN 10700 for PBP2 and PBP1a/b (concentration for 50% inhibition of penicillin binding [IC 50 ] = 0.1 and 1 mg/L, respectively) as revealed by competition experiments using membranes isolated from Escherichia coli. 14 The penem MEN 10700 also was investigated in bacterial isolates resistant to other antibiotics and showed activity against cefotaxime-resistant gram-negative strains (MIC 90 = 4 mg/L), 13 penicillin-resistant pneumococci (MIC 90 = 1 mg/L), 13 ciprofloxacin-resistant E. coli (MIC 90 = 0.25 mg/L), 21 and extended-spectrum ␤lactamase-producing strains of Klebsiella, Enterobacter, and Serratia sp (MIC 90 = 2 mg/L). 21 Time-kill kinetics of MEN 10700 against 12 penicillin-susceptible and penicillin-resistant pneumococci were similar to those of amoxicillin plus clavulanate relative to MIC values, with all 12 isolates killed after 24 hours incubation at 4 times MIC for both agents.…”
Section: Men 10700mentioning
confidence: 99%
See 1 more Smart Citation
“…This MRSA clone was first described in Spain, 1989(Dominguez et al 1994) and later on, in Portugal (Ferrari et al 2002), Italy and United Kingdom (Mato et al 1998), Germany (Witte et al 1994), Belgium, Switzerland, France (Deplano et al 2000), Poland (Leski et al 1998), Check Republic (Melter et al 2003), and United States (Roberts et al 1998a).…”
Section: Evolution Of Typing Techniques and The Characterization Of Mmentioning
confidence: 97%